Rock glacier and protalus rampart inventory in Las Salinas river basin, Central Andes of Argentina ... : الأنهار الجليدية الصخرية ومخزون سور البروتالوس في حوض نهر لاس ساليناس، جبال الأنديز الوسطى في الأرجنتين ... - Ana Paula Forte; Cristian Daniel Villarroel; María Yanina Esper Angillieri (OpenAlex, 2021)
This paper presents a detailed rock glacier and protalus rampart inventory from Las Salinas river basin, an arid subtropical mountain hydrological system (between 31°02' and 31°22' S latitude) located in the northern sector of the Central Andes of Argentina, where permafrost and cryogenic processes prevail. The inventory is based on a geomorphological characterization by means of optical remote sensing and field description data. The study region covers 630 km2, with 3.25% of the area containing 405±8.2 rock glaciers and protalus ramparts in total, of which 231±2.5 are considered protalus rampart and 49±2 are considered active, 61±1 inactive and 64±3 fossil rock glaciers. Frequency ratio and logistic regression were used as statistical methods to determine the relationship between the distribution of these periglacial landforms and different geological, morphometric and climatic variables as elevation, potential incoming solar radiation, slope, aspect and lithology. Results show that elevation, lithology, ... : تقدم هذه الورقة جردًا مفصلاً للأنهار الجليدية الصخرية والأسوار الأولية من حوض نهر لاس ساليناس، وهو نظام هيدرولوجي جبلي شبه استوائي قاحل (بين خطي عرض 31°02' و 31°22' S) يقع في القطاع الشمالي من جبال الأنديز الوسطى في الأرجنتين، حيث تسود التجمد الدائم والعمليات المبردة. ويستند الجرد إلى توصيف جيومورفولوجي عن طريق الاستشعار البصري عن بعد وبيانات وصف المجال. تغطي منطقة الدراسة 630 كم 2، مع 3.25 ٪ من المساحة التي تحتوي على 405±8.2 من الأنهار الجليدية الصخرية وأسوار البروتالوس في المجموع، منها 231±2.5 تعتبر سور بروتالوس و 49±2 تعتبر نشطة، 61±1 غير نشطة و 64±3 من الأنهار الجليدية الصخرية الأحفورية. تم استخدام نسبة التردد والانحدار اللوجستي كطرق إحصائية لتحديد العلاقة بين توزيع هذه التضاريس المحيطة بالجليد والمتغيرات الجيولوجية والمورفومترية والمناخية المختلفة مثل الارتفاع والإشعاع الشمسي الوارد المحتمل والمنحدر والجانب وعلم الصخور. تظهر النتائج أن الارتفاع وعلم الصخور والجانب هي العوامل الأكثر تأثيرًا لحدوث الأنهار الجليدية الصخرية النشطة. وفقًا للأنهار الجليدية الصخرية وتوزيع أسوار البروتالوس، فإن احتمال حدوث ...